What Indonesian Netizen Says about Covid-19 Vaccination? A Corpus Assisted Discourse Studies of YouTube’s Comment - Annada Nasyaya; Farisha Sestri Musdalifah; Yosi Arianti (Policy & Governance Review, 2023)
This research analyzes the views of the Indonesian people regarding Covid-19 vaccination through comments on the YouTube social media platform. This study aimed to analyze arguments, discussion patterns, attitudes, and views of the Indonesian people in the YouTube video comments at the start of the Covid-19 vaccination in Indonesia. Academically, this research provides in-depth information about the views of the Indonesian people on Covid-19 vaccination, which comes from online comments. This research is helpful for information providers and governments to make evidence-based policies and campaigns for effective communication strategies for vaccination programs. This study uses mixed methods by combining corpus linguistic methods with critical discourse analysis. Using the help of Antcont software, we analyzed 22,529 comments on the five videos about Covid-19 vaccination. The results showed various public views about vaccines; we found fifteen categories of comments: actors, health, media, rejection, acceptance, state, religious, mass, Islam, other countries, law, economy, region, knowledge, and politics. The contribution of this research is to fill in the gaps in the literature about people's reactions to vaccination in the context of social media. The implication of this research is to contribute to decision makers to take evidence-based policies to communicate Covid-19 vaccination.